PENGARUH GABUNGAN METODE DISKUSI DAN SIMULASI TERHADAP PERILAKU IBU DALAM PENGATURAN POLA MAKAN BATITA DI KELURAHAN KARANG SIRI KABUPATEN TIMOR TENGAH SELATAN TAHUN 2009 - Boymau, Yeni Y.; Lerik, M.D. Charlota; Manurung, Imeldha F. E. (Jurnal Pangan Gizi dan Kesehatan, 2010)
This research aims to assess the impact of a combination of discussion with a simulation method on mothers behaviour towards providing a nutritional diet for children under three years old at Kelurahan Karang Siri Kabupaten Timor Tengah Selatan. The subjects of this research are mothers of children under three years with malnutrition in Kelurahan Karang Siri Kabupaten Timor Tengah Selatan. Data were collected and calculated by a proportion formula of 20 %. The total number of respondents in this study is 22 mothers. This study used a quasi-experimental design with one group pre-tested post-tested. The data was gathered using questionnaire and interviews and the result was analyzed by Wilcoxon (ά = 0.05). Statistical analysis showed that there was a significant difference in mothers‘ knowledge for providing nutritional diet for children under three years old after combining the discussion and simulation method (p=0.000 < 0.05). This study found that the combination of discussion and simulation method had an impact on changing behaviour among mothers in providing nutritional diet for children under three years old at Kelurahan Karang Siri Kabupaten Timor Tengah Selatan in 2009.